Association between gut microbiota and psychiatric disorders: a systematic review - Grau-Del Valle, Carmen; Fernández, Javier; Solá, Eva; Montoya-Castilla, Inmaculada; Morillas, Carlos; Bañuls, Celia (Frontiers in Psychology, 2023)
Introduction In recent years, it has been described that the dysbiosis of the intestinal microbiota plays a transcendental role in several pathologies. In this sense, the importance of the gut microbiota in the gut-brain axis, with a bidirectional communication, has been demonstrated. Furthermore, the gut microbiota has been linked with mood disorders and neuropsychiatric disorders. Methods A systematic review of two databases – PubMed and Scopus – was carried out following PRISMA guidelines. We included original studies in humans with a control group published in the last 11 years, which were assessed by the Critical Appraisal Skills Program (CASP) to confirm their quality. Eighteen articles met all the selection criteria. Results A review of the articles revealed an association between psychiatric disorders and different bacterial phyla. The studies we have reviewed have demonstrated differences between subjects with psychiatric disorders and controls and highlight a clear relationship between depression, stress, autism spectrum disorder (ASD), psychotic episodes, eating disorders, anxiety and brain function and the gut microbiota composition. Conclusion A reduction of fermentative taxa has been observed in different psychiatric disorders, resulting in a decrease in the production of short-chain fatty acids (SCFAs) and an increase in pro-inflammatory taxa, both of which may be consequences of the exacerbation of these pathologies.